KREATIVITAS KOMUNIKASI PROGRAM DENDANG KELILING TVRI SUMATERA SELATAN - Muhammad Yudha Prayoga; Putri Citra Hati (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
The "Dendang Keliling TVRI South Sumatra" program is one of TVRI South Sumatra's initiatives which aims to maintain relevance with viewers in the ever-changing digital era. This program aims to elevate the artistic and cultural wealth of the South Sumatra region. This research uses a qualitative approach method by collecting data through participant observation during the program broadcast period, in-depth interviews with producers and members of the program production team, as well as content analysis of several episodes of "Dendang Keliling." The research results show that creativity in the communication of the "Dendang Keliling" program is reflected in the selection of in-depth themes, the use of social media as a means of two-way interaction with viewers, as well as close collaboration with local artists. This program succeeded in creating strong ties between TVRI South Sumatra and the local community, increasing understanding of regional culture, and increasing viewer engagement.